Usability Evaluation Model for Mobile Banking Applications Interface: Model Evaluation Process using Experts’ Panel - Abubakar, Hamisu Ibrahim; Hashim, Nor Laily; Hussain, Azham (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2016)
Many of the existing usability evaluation models for mobile applications have not been evaluated to determine its usefulness, accuracy and applicability in to the real world environment. This may not provide confidence on the side of the evaluator and the results may not be comprehensive and valid. A model for evaluating the usability of mobile banking applications interface is developed in response to usability practitioners and mbanking applications developers’ needs. The experts implemented the model using various m-banking application platforms through heuristic evaluation method. A list of predefined validation measures were used by the experts’ in order to determine the accuracy and applicability of the proposed model. The results show that the model is useful, accurate and can be used for evaluating the usability of m-banking applications interface. Therefore, this paper will benefit both the research community and the usability practitioners towards better understanding of model validation process.